May Measurement Month 2017: an analysis of blood pressure screening results from Australia—South-East Asia and Australasia. (24th April 2019) - Carnagarin, Revathy; Fonseca, Ricardo; Brockman, Derrin; Hering, Dagmara; Matthews, Vance B; Mihailidou, Anastasia; Reid, Christopher; Lee, Rebecca; Lambert, Gavin W; Burrell, Louise M; Sharman, James E; Xia, Xin; et al.
Abstract: Increased blood pressure (BP) is the single biggest contributing risk factor to the global disease burden. May Measurement Month (MMM) is a global initiative of the International Society of Hypertension aimed at raising awareness of high BP. In Australia, hypertension affects around six million adults and continues to remain the greatest attributable cause of cardiovascular mortality and morbidity (48.3%), stroke deaths (28%), and kidney disease (14%). An opportunistic cross-sectional survey was carried out during May 2017 predominantly in capital cities across Australia which included adult volunteers. Blood pressure measurement, the definition of hypertension and statistical analysis followed the standard MMM protocol. Additional information obtained included anthropometric data and responses to questionnaires on demographic, lifestyle, and environmental factors. Data were collected from 3817 individuals. After multiple imputation, of the 3758 individuals for whom a mean of the second and third BP reading was available, 1188 (31.2%) had hypertension. Of 3213 individuals not receiving antihypertensive treatment, 591 (18.4%) were hypertensive, and 239 (40.1%) of the 596 individuals receiving treatment had uncontrolled BP. Adjusted BP was higher in association with antihypertensive medication, cerebrovascular disease, smoking, and alcohol consumption. Blood pressure was higher when measured on the right arm and on Tuesdays. MMM17 was one of the largest BP screening campaigns undertaken in Australia using standardized BP measurements. In line with previous surveys, around one-third of screened adults had hypertension and approximately 40% of treated individuals remained uncontrolled. These results suggest that opportunistic screening can identify significant numbers with raised BP.